2013
DOI: 10.1016/j.bbrc.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the legumain gene by p53 in HCT116 cells

Abstract: Legumain (EC 3.4.22.34) is an asparaginyl endopeptidase. Strong legumain activity was observed in the mouse kidney, and legumain was found to be highly expressed in tumors. We previously reported that bovine kidney annexin A2 was co-purified with legumain and that legumain cleaved the N-terminal region of annexin A2 at an Asn residue in vitro and in vivo. In this study, we found a p53-binding site in intron 1 of the human legumain gene using computational analysis. To determine whether transcription of the leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…AEP plays important roles in regulation of the immune system (45) and in cancer (46,47) and has recently been shown to cleave the protein tau in Alzheimer's disease (48,49). In addition, its expression and activity are regulated by TP53 (50), and it cleaves peptide bonds carboxy terminal to asparagine (51). The asparagine residue of VDAC1 cleaved by AEP is exposed on the cytoplasmic side of the mitochondria, so this residue could come into contact with the contents of lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…AEP plays important roles in regulation of the immune system (45) and in cancer (46,47) and has recently been shown to cleave the protein tau in Alzheimer's disease (48,49). In addition, its expression and activity are regulated by TP53 (50), and it cleaves peptide bonds carboxy terminal to asparagine (51). The asparagine residue of VDAC1 cleaved by AEP is exposed on the cytoplasmic side of the mitochondria, so this residue could come into contact with the contents of lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis by mass spectrometry of VDAC1-ΔC showed cleavage at asparagine 214 and glycine 213. Of note, AEP is also regulated by TP53 (56). Moreover, we reported that BNIP3, already known to be involved in regulating mitochondria morphology in hypoxia (36), acted as a docking site for lysosomes together with clathrin, a protein involved in multiple membrane vesicle trafficking pathways (57).…”
Section: The Hypoxic Mitochondrial Phenotype and Vdac1-δcmentioning
confidence: 99%
“…Alginates can accelerate the autocatalytic activation of pro-LGMN at pH 4.0 and 5.0 8 , with their activities increasing upon exposure to doxorubicin and reducing following knock-down of p53 9 . Similarly, intracellular LGMN activity is decreased by internalization of cystatin E/M 10 .…”
mentioning
confidence: 99%